Development of a Low-Cost, Short-Range Radar System to Measure Speed and Distance - Parra, Yolanda G.; Guzmán B., Tomás; González P., José Tomás (TECCIENCIA, 2017)
The aim of this project consists in designing and implementing a short-range, low-cost K band, continuous wave radar prototype system for industrial applications with the K-LC6 module, capable of measuring distance and radial speed. This article describes all the hardware and software design, manufacture, and implementation considerations of the radar system. To minimize the cost of a potential product for industry, prototype hardware was implemented by using commercial elements. This work also shows the result of experimental tests that permitted characterizing the prototype and verifying measurements of distance and speed of targets in laboratory environments. These tests permitted verification of its operation, obtaining a short-range (from 0.6 to 63 m) frequency modulated - continuous wave radar prototype, capable of measuring speeds up to 9.2 km/h.